Molecular and Epidemiological Evaluation of Liver Function Diagnosis between Different Genotypes of HBV and HCV in Non-Responders of HBV-HCV Co-Infected Patients with Healthy Controls - Ihteshamul Haq, Fazli Zahir, Mohsina Haq, Ronaq Zaman, Arbab Muhammad Kashif Khan, Naumana Rehman, Ibrar Ahmad, Hakeem Jan, Zeeshan Nasar, Hassan Arif, Zeeshan Ahmad (Pakistan Journal of Medical & Health Sciences, 2022)
Hepatitis B and C co-infection may leads to cirrhosis resulting in hepatocellular carcinoma with poorer survival rate. Pegylated interferon and ribavirin treatment is considered as gold standard. Despite of adequate treatment, some patients remained nonresponders. Due to this reason, this study was designed to compare different parameters of liver function tests along with HBV- HCV genotyping in non-responders of HBV-HCV co-infection with normal controls. Study population was divided in two groups. Group A (patient group) includes 30 HBV-HCV co-infected patients and Group B (control group).includes 30 normal individuals. Blood samples of both groups were collected. Samples were analyzed for HBV and HCV genotyping using automated kits of Abbott laboratories and Liver Functions testing (ALT, ALP, Bilirubin, Albumin) using ROCHE COBAS-501 automated system. Statistical analysis using chi-square test for ordinal data and t-test for numerical data was used using p value.